Alternative sources of protein in the food industry - Fursik, Oksana; Strashynskyi, Igor (My University, 2020)
According to the FAO report in 2009, “How to Feed the World in 2050,” global food production is expected to increase by about 70% in 2050 [1]. According to a review of world agriculture in 2012 until 2030/2050, in order to satisfy the nutrition of a growing population, the total volume of meat production should be increased from 258 million tons in 2005 to 455 million tons by 2050. For milk and eggs to 1077 and 102 million tons by 2050 respectively [2]. Similar trends have been observed for other high-quality protein sources. These forecasts show a significant increase in protein demand, to meet the growing population and well-being of countries with emerging economies.
Keywords: кафедра технології м’яса і м’ясних продуктів; meat; protein; biological processes